Data Visualization of Development Improvement and Budget Assistance for Village Residents Using the R Studio Program in Jombatan Village, Jombang District - Isrofi, Isrofi; Zulfikar, Zulfikar (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Indonesia is a country that implements a regional self-government system, where each region is given the freedom to manage an exclusive area. This sovereignty does not only apply at the provincial and regional levels but also includes villages. Implementing